Analytical performance evaluation of the Elecsys® Cyclosporine and Elecsys® Tacrolimus assays on the cobas e411 analyzer - Sasano, Maki (Pract Lab Med, 2017)
BACKGROUND: Cyclosporine (CsA) and tacrolimus (TAC) are immunosuppressant drugs that are often used to treat autoimmune diseases and as transplantation therapy; therefore, their concentrations need to be monitored carefully. We herein evaluated the analytical performance of the Elecsys® Cyclosporine and Elecsys® Tacrolimus assay kits, which have been newly developed to measure CsA and TAC concentrations in the whole blood. METHODS: We used residual whole blood samples from autoimmune disease and transplantation patients who were being treated with CsA or TAC. CsA concentrations were measured using an affinity chrome-mediated immunoassay (ACMIA) and an electrochemiluminescence immunoassay (ECLIA). TAC concentrations were measured using a chemiluminescence immunoassay (CLIA) and ECLIA. We investigated assay precision, linearity, lower limit of quantitation (LOQ), stability of calibration, influence of interference substances and the hematocrit, correlation of ACMIA with ECLIA, and correlation of CLIA with ECLIA. RESULTS: Within-assay coefficients of variation were 1.8−3.6% (CsA: 94−1238 ng/mL) and 2.9−3.9% (TAC: 2.1−17.8 ng/mL), whereas day-to-day coefficients of variation ranged between 3.0−4.1% (CsA) and 2.8−3.9% (TAC). The limits of quantitation were defined as the concentration at which the CV was approximately 10%. Each lower LOQ obtained was 16 ng/mL (CsA), and 0.95 ng/mL (TAC). CsA and TAC calibrations were stable for at least 21 days. Neither the presence of conjugated bilirubin, unconjugated bilirubin, chyle, and rheumatoid factor nor the hematocrit affected these assays. A method comparison using a standardized major axis regression analysis of ACMIA and ECLIA was r=0.995, y=0.924x −1.175, n=200 (CsA), while that of CLIA and ECLIA was r=0.994, y=1.080x −0.197, n=200 (TAC). CONCLUSIONS: The analytical performances of the Elecsys® Cyclosporine and Elecsys®Tacrolimus assays were acceptable. Furthermore, CyA and TAC concentrations may be simultaneously measured using a single pretreatment which is of benefit if patients have to undertake conversion between these two drugs. Additionally, it benefits the workflow in the clinical laboratory. Thus, the Elecsys® Cyclosporine and Elecsys® Tacrolimus assays may be suitable for routine therapeutic drug monitoring.